2017
DOI: 10.18632/oncotarget.19614
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive microRNA-sequencing of exosomes derived from head and neck carcinoma cellsin vitroreveals common secretion profiles and potential utility as salivary biomarkers

Abstract: Exosomes are nano-scale, membrane encapsulated vesicles that are released by cells into the extracellular space and function as intercellular signaling vectors through horizontal transfer of biologic molecules, including microRNA (miRNA). There is evidence that cancer-derived exosomes enable the tumor to manipulate its microenvironment, thus contributing to the capacity of the tumor for immune evasion, growth, invasion, and metastatic spread. The objective of this study was to characterize differential secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 51 publications
3
88
0
Order By: Relevance
“…Currently, the study of salivary biomarkers has developed beyond oral diseases 84 - 86 to systemic diseases 87 , 88 , which has broadened the potential for systemic disease detection 89 , 90 . Recently, Langevin et al 91 , using miRNA sequencing, found that several salivary exosomal miRNAs, including miR-486-5p, miR-486-3p, and miR-10b-5p, were substantially overexpressed among a subset of head and neck squamous cell carcinoma patients compared to cancer-free controls, highlighting the use of salivary exosomal miRNAs as potential noninvasive cancer biomarkers. Zheng et al 70 used liquid chromatography tandem mass spectrometry to identify the contents of salivary exosomes in patients with inflammatory bowel disease (IBD), which is an intestinal immune-dysfunctional disease with unknown cause.…”
Section: Correlation Between Salivary Exosomes and Systemic Diseasesmentioning
confidence: 99%
“…Currently, the study of salivary biomarkers has developed beyond oral diseases 84 - 86 to systemic diseases 87 , 88 , which has broadened the potential for systemic disease detection 89 , 90 . Recently, Langevin et al 91 , using miRNA sequencing, found that several salivary exosomal miRNAs, including miR-486-5p, miR-486-3p, and miR-10b-5p, were substantially overexpressed among a subset of head and neck squamous cell carcinoma patients compared to cancer-free controls, highlighting the use of salivary exosomal miRNAs as potential noninvasive cancer biomarkers. Zheng et al 70 used liquid chromatography tandem mass spectrometry to identify the contents of salivary exosomes in patients with inflammatory bowel disease (IBD), which is an intestinal immune-dysfunctional disease with unknown cause.…”
Section: Correlation Between Salivary Exosomes and Systemic Diseasesmentioning
confidence: 99%
“…For example, exosomal miR‐486 and miR‐10b‐5p, which may participate in suppression of immune pathways and reprogramming of cellular metabolism, have been found at elevated levels in saliva of head and neck squamous cell carcinoma (HNSSC) patients. This result demonstrates that these exosomal miRNAs may serve as non‐invasive salivary biomarkers of HNSCC (Langevin et al, ). Rabinowits et al () also screened some exosomal miRNAs from both tumor samples and plasma of patients with tongue SCC as diagnostic biomarkers for tongue SCC.…”
Section: Evs In Oral and Salivary Gland Cancer Diagnosis And Therapymentioning
confidence: 64%
“…Comparison of the microRNA present in exosomes isolated from the conditioned media from 4 HNSCC cell lines: H413 (from buccal mucosa OSCC), Detroit 562 (pharyngeal cancer metastatic to pleura), FaDu (hypopharyngeal cancer) and Cal 27 (tongue OSCC), with similarly isolated EVs from normal gingival keratinocytes identified 32 common differentially abundant microRNA in the 4 HNSCC cell lines [56]. Further, comparison of the microRNA present in EVs isolated from the saliva of OSCC patients (n = 5) and 5 cancer-free controls found several of the microRNA that were upregulated in cancer culture cells were increased in salivary exosomes of HNSCC patients when compared to controls [56].…”
Section: Directed Microrna Cargo Of Oscc-derived Evsmentioning
confidence: 99%